Maruyama Masao : and the Fate of liberalism in Twentieth-Century Japan - Tadashi, Karube; Noble, David (Tokio, Japan : Internacional House of Japan, 2008)
The Fate of a Thinker -- A taisho Kid -- In a politicized age -- From war to postwar -- Conceiving postwar democracy -- Politics and humanity in the contemporary world -- The sense of otherness -- Chronology -- Notes.
Karube demonstrates the influence of Maruyama's personal experiences on the development of his political philosophy. For example, Maruyama turned to the study of neo-Confucian Japanese thinkers such as Ogyū Sorai (1666–1728) in 1940, when he produced a brilliant alternative history to counter the celebrations of “the timeless Japanese national spirit” then dominant in Japan. Maruyama's analysis of Ogyū focused attention on the ethical underpinnings of political thought as well as the diversity of the Japanese intellectual tradition. I had always assumed that Maruyama turned to this topic because it was safer than modern ones, a tactic deployed by many other scholars at the time. On the contrary, as Karube explains, his research was not safe at all. Maruyama wrote this history as the main text for a new college course, approved by the Ministry of Education in 1939, that was supposed to indoctrinate students in “national polity studies” (kokutaigaku). His professor, Nanbara Shigeru, hired Maruyama both to develop the curriculum and to teach the course, but Maruyama was actually the second person to be offered this opportunity. The first, Tsuda Sōkichi, who had focused on ancient Chinese and Japanese thought as a visiting scholar in 1939, was relentlessly attacked as unpatriotic and the following year lost his job at Waseda University, had four of his books banned, and was prosecuted for violating publishing laws. In the summer of 1944, at the age of thirty, Maruyama, unlike nearly all of his colleagues, was drafted, probably as punishment for his views. In addition, he was inducted as a private, not an officer. Maruyama probably could have volunteered for officer's training but was too stubborn. He paid dearly for this gesture. Japanese Imperial Army officers were notorious for the harsh treatment they meted out to enlisted men—especially highly educated ones—and Maruyama was beaten and starved to the point where he collapsed from beriberi, a vitamin deficiency caused by malnutrition. Maruyama's ill-treatment took place while he was in basic training in Japan, not at the battlefront, and, ironically, probably saved his life by keeping him in the hospital when his regiment departed for Korea (p. 87). Karube provides a new explanation for the intensity of Maruyama's interest in the question of why individuals accepted fascism. In the early 1950s, Maruyama began focusing less on the ways in which groups of citizens could reshape political institutions and more on the uniqueness of individual experience, rather than a common national or modern identity. Karube argues that this shift was occasioned in part by Maruyama's lengthy sojourn of over two years (in two stints) in a Tokyo hospital for tuberculosis sufferers. That experience, argues Karube, “deepened his understanding” that people tended to act on the basis of “their images of the world and to have difficulty communicating with people holding different world views,” and, more importantly, that this difficulty was “not limited to political conflict, but frequently occurs in the midst of everyday life” (p. 138). Maruyama's last decades were a bit sad: as Karube explains, Maruyama's ideas had made enormous sense to other Japanese until about 1970, but from then on younger people found him frustratingly old-fashioned, and Maruyama withdrew from public life, writing less and less. Maruyama's own image of the world was deeply rooted in his personal experiences, which corresponded to that of many others of his generation. Young people, unfamiliar with either wartime oppression or the grinding poverty that had accompanied it, saw public life in different ways. Issue Section: Asia
Resumen tomado del sitio web de la editorial
Incluye bibliografía
General
Keywords: Masao, Maruyana -- 1914-1996; Historia contemporánea -- 1914 -- Japón -- Siglo XX; Liberalismo; Filosofía; Biografías